Avaliação pré-clínica do perfil farmacocinético do complexo de rutênio II/ triptofano em ratos por espectrofotometria UV-Vis - Zoghaib, Alarisse Arçari Fachetti (2015)
The ruthenium (II)/amino acid complex (rutrpII) demonstrated high anticancer activity against murine breast cancer (tumor of Ehrlich) in vitro and in vivo, and increased the median survival of animals. There was then necessary to investigate the pharmacokinetic parameters of the drug prototype as a requirement to pre-clinical knowledge of it. This study aimed to obtain the pharmacokinetic profile of ruthenium (II) / tryptophan administered to rats intraperitoneally in a single dose by quantifying this substance in plasma using validated analytical methodology in UV-VIS spectrophotometer. The methodology consisted of the administration of the prototype rutrpII to 3 rats at a dose of 6 mg/kg, intraperitoneally. Samples of blood 1.0 ml were collected by cannulation of the left jugular vein with heparinized syringe, the intervals from 0 to 9 hr. After centrifugation the plasma was frozen at -20 until the time of analysis. The bioanalytical method to quantify rutrpII was developed and validated in UV-VIS at a wavelength of 417 nm. From the construction of the concentration versus time curve, the kinetic parameters were calculated (Software WinNonlin 5.0 (Pharsight ™) Results were: Tmax = 8 h, Cmax = 169.86 mg/mL, t1/2 = 1.04 ± 0.02 h, ClT/F = 1.32 ± 0.05 mL/min/kg, Vd/F = 1,98 ± 0,05 L/kg. The developed and validated bioanalytical method was suitable for the detection and quantification of RutrpII in rat plasma. The values of pharmacokinetic profiles found, and extrapolated on allometric scaling allow us to understand that the compound studied showed a slow tissue distribution profile and / or was eliminated slowly (Vd low and low value CLT), due to a possible affinity between RutrpII and plasma proteins. This affinity may be explained by the similarity of their chemical structure with iron, enabling it to be transported by biomolecules such as transferrin, albumin or any other, and having as a target the DNA of cancer cells. In general, the compounds of ruthenium (II) / amino acids may be promising drugs for the amino acids present in the complex, may facilitate the recognition of the complex as a whole by DNA, and thus less toxic.